The Risk Factors of Patients with Cruris Fracture Nonunion in Dr. Mohamad Soewandhie Hospital in 2021-2022: A Case-Control Study - Clarissa, Regina; Sasono, Bimo; Juliasih, Ni Njoman ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2024)
Background: The crural region is highly susceptible to injury in Indonesia, with fractures being a common occurrence. If not properly treated, these fractures can lead to complications such as nonunion. To investigate the risk factors for nonunion cruris fractures, this study was conducted at Dr. Mohamad Soewandhie Hospital, examining age, gender, working status, education, trauma mechanism, and previous treatment history.Methods: This case-control study analyzed patient records from 2021 - 2022 at Dr. Mohamad Soewandhie Hospital, comparing 12 nonunion and 24 union cruris fracture cases. Data on age, gender, work, education, trauma, and treatment history was collected between August and October 2023. Statistical analysis was performed using the Mcnemar and Wilcoxon tests, with a significance level of p < 0.05.Results: A study of 149 cruris fractures found 12 nonunions, primarily affecting males aged 26-45 or 46-65. Notably, the highest nonunion rate (41.7%) was in the 12-25 age group (p = 0.027). Males were more affected, with 7 nonunion cases (58.3%) (p = 0.041). Working class patients had the highest fracture and nonunion rates (83.3%) (p < 0.001). High school education was most common among nonunion cases (75%) (p = 0.374). High-energy trauma was reported in almost all nonunion cases (91.7%) (p < 0.001). All nonunion patients had a history of ORIF (p = 0.102).Conclusions: The study revealed that age, gender, work status, and trauma mechanism significantly influenced nonunion cruris fractures at Dr. Mohamad Soewandhie Hospital in 2021-2022. Patient education and past treatment history had no significant impact.